Research Trend of PBL and PjBL in Bibliometric Analysis: Implications for a Better Future of Physics Education - Dwikoranto; I R Dawana; Rahyu Setiani (Indonesia Approach Education, 2024)
This research investigates the growing research trends surrounding the application of Problem-Based Learning (PBL) and Project-Based Learning (PjBL) in the Physics Education domain. Using a bibliometric analysis approach, data sourced from the Scopus database yielded 89 related documents. The findings revealed a significant surge of scholarly interest in the implementation of PBL and PjBL in Physics Education over the past decade, indicating a growing area for further exploration. In particular, there is a growing trend to integrate PBL and PjBL methodologies with STEM education, as this incorporation has shown promise in enhancing critical thinking, problem-solving abilities, and student engagement. However, it's important to note that this researh was constrained by its dependence on a sole database, namely Scopus, for the collection of data. Future research efforts in PBL and PjBL in Physics Education are encouraged to utilise diverse databases to ensure comprehensive coverage and analysis.